Necrotizing Enterocolitis with Perforation in an Extreme Preterm, Extremely Low Birth Weight Neonate - Gopalakrishnan, Shridhar; Singh, Shailendra; Sodhi, Kirandeep; Arora, Manu (Journal of Nepal Paediatric Society, 2016)
Necrotizing enterocolitis (NEC) remains the most common and serious surgical condition among preterm, very low birth weight neonates with a mortality of 40% to 50% in those requiring surgery. We report perforation secondary to NEC in an extreme preterm, extremely low birth weight neonate with a good outcome due to aggressive surgical management and intensive care. J Nepal Paediatr Soc 2016;36(2):201-203.